Moda em desconstrução pela arte - Stürmer, Marieli Patta (Universidade do Vale do Rio dos Sinos, 2019)
The present work aims to analyze the contemporary fashion as an expression of art, from the conceptual and avant garde creation of the Japanese stylist Rei Kawakubo. From the research in the specialized bibliography and observation of the exhibition held by the curatorship of the Metropolitan Museum of New York, which presented to the public in 2017 the work of this creator, this project seeks to analyze her work as artistic expression, as well as understand the relationship between art and contemporary fashion, through the vision of its creator. As an inspiration for the creation of the fashion collection that conveys the concepts of the brand idealized by this stylist, aspects of the wabi sabi and its origins in the tea ceremony were brought as a way to translate the aesthetics that guides her creations for the target audience.
Keywords: Moda; Arte; Vanguarda; Rei Kawakubo; Wabi sabi; Fashion; Art; Avant garde